Media Guru Pendidikan Agama Islam dalam Membentuk Karakter Religius Siswa di SMP IT Mutiara Aulia - Abu A’la Al Maududi; Salminawati Salminawati (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to describe and analyze the role of learning media used by Islamic Religious Education (PAI) teachers in shaping students' religious character at SMP IT Mutiara Aulia through the integration of teacher exemplary behavior (uswah hasanah) and smartboard-based digital media. A descriptive qualitative approach was employed, utilizing observation, interview, and documentation techniques for data collection. The subjects consisted of one PAI teacher (Mrs. S) and three students (F, D, R). The findings indicate that teacher exemplarity plays a vital role in internalizing religious values by providing affective and transformative learning experiences. Furthermore, the use of visual and audiovisual media received positive responses from students, as evidenced by increased enthusiasm and active participation during lessons. Qualitative data were descriptively analyzed through data reduction, data display, and conclusion drawing/verification stages to systematically illustrate the role of PAI learning media in student character development. The media proved effective in instilling religious values, including discipline, honesty, politeness, and responsibility. Despite encountering technical challenges related to facility readiness and internet connectivity, the implementation of varied learning media is proven to enhance the understanding of religious values and accelerate the formation of students' religious character.